Description of a new Mummucina species (Solifugae: Mummuciidae) from Peru - Cossios, E. Daniel (2020)
A new species of Mummuciidae, Mummucina chaskae, collected at 1946 m.a.s.l. in the department of Huanuco, Peru, is described and illustrated. With this description, the number of known species of Mummucina rises to five for the genus and to three for Peru. Publicación registrada en Zoobank/ZooBank article registered:LSIDurn:lsid:zoobank.org:pub:992B1B6B-1938-4197-A50D-BB850924A9CAActo nomenclatural/nomenclatural act:Mummucina chaskae Cossios, 2020LSIDurn:lsid:zoobank.org:act:B0FAEACD-2D22-42FE-8D87-F8BA9E2AC360